A phase I dose‐escalation study to assess safety, tolerability, pharmacokinetics, and preliminary efficacy of the dual mTORC1/mTORC2 kinase inhibitor CC‐223 in patients with advanced solid tumors or multiple myeloma. Issue 19 (15th July 2015) - Bendell, Johanna C.; Kelley, Robin K.; Shih, Kent C.; Grabowsky, Jennifer A.; Bergsland, Emily; Jones, Suzanne; Martin, Thomas; Infante, Jeffrey R.; Mischel, Paul S.; Matsutani, Tomoo; Xu, Shuichan; Wong, Lilly; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The mammalian target of rapamycin (mTOR) pathway is essential for tumor development, yet mTOR inhibitors have yielded modest results. This phase 1 study investigated the mTORC1/mTORC2 inhibitor CC‐223 in patients with advanced cancer. METHODS Patients with advanced solid tumors or multiple myeloma received an initial dose of 7.5‐60 mg of CC‐223, followed by oral daily dosing in 28‐day cycles until disease progression. The primary objective was to determine the safety, tolerability, nontolerated dosage, maximum tolerated dosage (MTD), and preliminary pharmacokinetic profile. Secondary objectives were to evaluate pharmacodynamic effects and to describe preliminary efficacy. RESULTS Twenty‐eight patients were enrolled and received ≥1 dose of CC‐223. The most common treatment‐related grade 3 adverse events were hyperglycemia, fatigue, and rash. Four patients had dose‐limiting toxicities, including hyperglycemia, rash, fatigue, and mucositis. Therefore, 45 mg/d was determined to be the MTD. The pharmacokinetics of CC‐223 demonstrated a mean terminal half‐life ranging from 4.86 to 5.64 hours and maximum observed plasma concentration ranging from 269 to 480 ng/mL in patients who received CC‐223 ≥45 mg/d. Phosphorylation of mTORC1/mTORC2 pathway biomarkers in blood cells was inhibited by CC‐223 ≥30 mg/d with an exposure‐response relationship. Best responses included 1 partial response (breast cancer; response duration 220 days; 30‐mg/d cohort), stable disease (8 patients across ≥15 mg/d cohorts; response duration range, 36‐168 days), and progressive disease (12 patients). The disease control rate was 32%. CONCLUSIONS CC‐223 was tolerable, with manageable toxicities. Preliminary antitumor activity, including tumor regression, and evidence of mTORC1/mTORC2 pathway inhibition were observed. Cancer 2015;121:3435–43. © 2015 American Cancer Society.